Vermiremediation and mycoremediation of polycyclic aromatic hydrocarbons in soil and sewage sludge mixture: a comparative study - Azizi, A.B.; Liew, K.Y.; Noor, Z.M.; Abdullah, N. (2013)
Polycyclic aromatic hydrocarbons-contaminated soil and sewage sludge mixtures in microcosms were tested separately in triplicate with two types of biological agents, namely earthworms (Lumbricus rubellus) and spent fungal mycelia of Pleurotus sajor-caju (SPC) for 60 days. The results indicated that vermiremediation (VMR) and mycoremediation (MYC) showed degradation result of 99.99 PAHs i.e. Anth, Phen and BaP removal. Ten earthworms and 750 g of SPC depicted optimum results in nutrient element content among respective treatments. Treatment of MYC resulted a consistence increment of soil macronutrients except for TP and TKN (500 g treatment) compared to VMR. Hence, sixty days incubation of spent fungal mycelia of Pleurotus sajor-caju compost (SPC) is potential to degrade 99.99 of Anth, Phen and BaP but at the same time enrich the soil macronutrients i.e. TOC, TKN and TK